A study on political aspect of South China Sea dispute : South China Sea maritime territorial disputes - Lee, Siew Bee (2017)
This paper seeks to examine the art and science of politics in shaping the South China Sea dispute and consequently its impact at large on the maritime industry. It further provides recommendations to solve the root issue in an attempt to minimise the impacts. This is done through an extensive qualitative research and interview with industry veterans and political researchers. Findings shows how countries’ political system and politicians’ character alters the diplomatic relationship between China, claimant and non-claimant states. Philippines benefitted greatly in economic terms after cooperating with China, USA is taking on a tough stance which heightens the possibility of World War III, whereas Singapore is losing favour from China because of its support for international law. As a result, regional trade relations, maritime environment and security is affected. There is no ‘one size fits all’ strategy and it would be too ambitious to solve the dispute, instead advice which each countries can adopt is given. As the situation in the South China Sea is ever-changing, the applicability of this paper is limited to the current situation and continuous study needs to be done to complement this paper.